Binge eating and purging in first‐year college students: Prevalence, psychiatric comorbidity, and academic performance. Issue 3 (23rd December 2019) - Serra, Riccardo; Kiekens, Glenn; Vanderlinden, Johan; Vrieze, Elske; Auerbach, Randy P; Benjet, Corina; Claes, Laurence; Cuijpers, Pim; Demyttenaere, Koen; Ebert, David D; Tarsitani, Lorenzo; Green, Jennifer Greif; et al.
Abstract: Background: Binge eating and purging behaviors (BPB) are common among college students, but evidence is scant on prevalence and associations of BPB with mental health problems and objective academic performance. This study aims to investigate: (a) 12‐month prevalence of BPB among college first‐year students, (b) comorbidity patterns of BPB with various mental health problems, and (c) the association of BPB with objective academic functioning. Methods: Using data from the Leuven College Surveys (Belgium), as part of the World Mental Health Surveys International College Student initiative, we cross‐sectionally assessed 12‐month BPB and mental health problems among college first‐year students ( n = 4, 889; response rate = 73.2%) at the beginning of the academic year. Objective measures of academic functioning (final grades, expressed in academic year percentage "AYP" [0–100%] and academic failure) were obtained from administrative records at the end of the academic year. Results: Twelve‐month prevalence of BPB was 7.6% (7.3%binge eating and 1.0%purging), with higher rates among females than males. Bivariate models showed an association between BPB and numerous mental health problems (ORs = 3.4–18.4). Multivariate models showed associations with non‐suicidal self‐injury, post‐traumatic stress, internalizing/externalizing problems and suicidal ideation. After controlling for sociodemographic characteristics and comorbid mental health problems, BPB were still associated with lower AYP (−4.1 to −11.2% range) and elevated odds of academic year failure (ORs = 1.4–4.2). Conclusions: BPB (especially binge eating) are relatively common and associated with mental health problems, comparatively low academic performance, and higher risk of academic failure among college first‐year students. Further study is needed to examine the causal dynamics underlying these associations.